Religiosity and its Relationship with the Tolerance Attitudes of Higher Education Students - Fuad, A. Jauhar; Masuwd, Mowafg (Tribakti: Jurnal Pemikiran Keislaman, 2023)
This study aims to examine the relationship between religiosity and tolerance among university students. This research focuses on how university students’ level of religiosity relates to their attitudes towards differences in religion, culture, and views in the academic environment. The research method was a quantitative approach with a cross-sectional design. This study involved 160 students from various programs at several universities. Data were collected using a questionnaire consisting of a religiosity measurement scale and tolerance attitude measurement scale. The religiosity measurement scale includes the dimensions of belief, involvement in religious activities, and importance of religion in daily life. The tolerance attitude measurement scale assessed students' responses to statements describing openness, appreciation, and respect for differences. The results of the analysis show a positive correlation between the level of religiosity of university students and their tolerance attitudes. Students who showed higher levels of religiosity tended to have more tolerant attitudes. These findings suggest that religion can act as an important factor in shaping students' social attitudes in the academic environment. This study contributes to the understanding of the role of religion in shaping tolerant attitudes among university students. The implications of these findings can help in designing more inclusive education programs that emphasize openness to differences and respect for diversity. In addition, this study underscores the importance of opening dialogue and facilitating faith in higher education settings. Although the findings provide valuable insights, this study has limitations in terms of sample coverage and geographical area. Further research involving larger and more diverse samples from different countries or regions is expected to corroborate and expand the generalizability of these findings. Future research could also explore other factors that may influence the relationship between religiosity and tolerance among university students.